Latin-American women writers class, race, and gender - Jehenson, Myriam Yvonne - (Albany State University of New York Press, 1995)
""Study examines class, race, and gender in literature,concentrating on 1950s. Offers comparison with European writers, which helps to illuminate our understanding of Julieta Campos, Luisa Valenzuela, Cristina Peri Rosi, Helena Perente Cunha, Rigoberta Menchú, Domitila Barrios, and Carolina María de Jesus"--Handbook of Latin American Studies, v. 58.|uhttp://www.loc.gov/hlas
Includes bibliographical references (pages 177-191) and index
Keywords: Women and literature -- Latin America -- History -- 20th century; Feminism in literature; Women in literature; Race in literature; Social classes in literature